Review of Mesozoic Perissommatidae (Insecta: Diptera) - Lukashevich, Elena D.; Blagoderov, Vladimir A. (Zootaxa, 2020)
Perissommatidae is a peculiar relict nematoceran family with one extant genus inhabiting Australia and South America. The family is known since the Middle Jurassic, but the fossil record is very poor and is restricted to Asia. The description of three species of Collessomma gen. nov. from Lower Cretaceous of Transbaikalia and Mongolia—C. sibirica sp. nov., C. gnoma sp. nov., and C. mongolica sp. nov.—expands our understanding of the family in the Mesozoic, when Perissommatidae were much more diverse morphologically and spread geographically then now. Two previously described genera Gurvaniella Kovalev, 1986 and Limnorhyphus Hong, 1983 are transferred to the Perissommatidae.